Detection of human ovarian carcinoma from blood samples using scent dogs - Alves,João (2019)
Ovarian cancer is the most lethal of all common gynecologic malignancies, with more than 204,000 new cases and 125,000 deaths/year worldwide. Currently, there are no acceptable screening techniques available. Body odors are the result of volatile organic compounds that are originally secreted from various cells. Tumors likely have distinctive odors that can be recognized by trained dogs. In a double-blinded test, three detection dogs were trained to identify blood samples obtained from patients with ovarian carcinoma. Animals where presented to three equal copies of five different test sets, each comprising five samples. Each set had a positive target sample, non-ovarian malignant tumor sample(s), healthy donors sample(s) or benign tumor sample(s). Individual success rate was 40%, while if an identification was considered when two or more dogs mark the same sample, success reached 60%. A malignant sample was identified 64.45% of the times. If the identification was made by two dogs at the same time, malignant samples were identified 80% of the times. The present study consists, in the authors knowledge, the first description of the use of scent dogs to detect ovarian tumors from blood samples, when up against blood samples containing any other possible type of tumor.